Bioremoval of chromium from wastewater of tannery factory in Iraq (Baghdad Science Journal, 2025)
Bioremoval of chromium from wastewater of tannery factory in Iraq was studied. The bacteria Proteus vulgaris 7E showed an enhanced capability in biosorping chromium when its concentration increased in the solution, reaching a maximum of 476,7 mg/ ml out of 492 mg/ ml under optimum conditions at pH 6 and 50°C at one hour contact time and biomass of 1 mg/ml.The present results showed that dead cells of P. vulgaris 7E biosorbed 87.41 mg/ml of chromium in comparison with91.18 mg/ml of chromium biosorbed by living cells, this indicates the insignificant effect of physiological state of cells.It was found that the above biosorption is physico-chemical process depends upon electrostatic attraction forces.The results has illustrated that the most efficient eluting solution was 0.1M HCL which recovered 85% of biosorbed chromium.P. vulgaris 7E was able to remove completely all chromium from the waste water taken from tannery factory.